Spectacular batesian mimicry in ants - Hashim, Rosli; Ito, F.; Billen, J.; Huei, Y.S.; Kaufmann, E.; Akino, T. (2004)
The mechanism by which palatable species take advantage of their similarity in appearance to those that are unpalatable, in order to avoid predation, is called Batesian mimicry. Several arthropods are thought to be Batesian mimics of social insects; however, social insects that are Batesian mimics among themselves are rare. In Malaysia we found a possible Batesian mimic in an arboreal ant species, Camponotus sp., which was exclusively observed on foraging trails of the myrmicine ant Crematogaster inflata. The bright yellow and black colouring pattern, as well as the walking behaviour, were very similar in both species. We observed general interactions between the two species, and tested their palatability and the significance of the remarkably similar visual colour patterns for predator avoidance. Prey offered to C. inflata was also eaten by Camponotus workers in spite of their being attacked by C. inflata, indicating that Camponotus sp. is a commensal of C. inflata. An experiment with chicks as potential predators suggests that Camponotus sp. is palatable whereas C. inflata is unpalatable. After tasting C. inflata, the chicks no longer attacked Camponotus sp., indicating that Camponotus sp. is a Batesian mimic of Crematogaster inflata.